2022
DOI: 10.3390/ijms232415712
|View full text |Cite
|
Sign up to set email alerts
|

Menadione Potentiates Auranofin-Induced Glioblastoma Cell Death

Abstract: Glioblastoma (GBM) is the most aggressive primary brain tumor. Recently, agents increasing the level of oxidative stress have been proposed as anticancer drugs. However, their efficacy may be lowered by the cytoprotective activity of antioxidant enzymes, often upregulated in ne-oplastic cells. Here, we assessed the mRNA and protein expression of thioredoxin reductase 1 (TrxR1), a master regulator of cellular redox homeostasis, in GBM and non-tumor brain tissues. Next, we examined the influence of an inhibitor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…Moreover, Van Loenhout et al showed that adherent GBM cells were more sensitive to auranofin (AF), an inhibitor of antioxidant thioredoxin reductase, than the relevant cells cultured in neurospheres [46]. Similarly, in our previous study, LUB17N cells showed increased resistance to AF compared to their counterparts cultured as an adherent monolayer [47].…”
Section: Discussionsupporting
confidence: 55%
“…Moreover, Van Loenhout et al showed that adherent GBM cells were more sensitive to auranofin (AF), an inhibitor of antioxidant thioredoxin reductase, than the relevant cells cultured in neurospheres [46]. Similarly, in our previous study, LUB17N cells showed increased resistance to AF compared to their counterparts cultured as an adherent monolayer [47].…”
Section: Discussionsupporting
confidence: 55%
“…Auranofin, an FDA-approved oral drug, known for its clinical safety, is able to penetrate the blood-brain barrier at doses ranging from 0.2 to 5 µmol/L [115]. Inhibition of thiol redox enzymes and inflammation pathways commonly involved in tumor growth instigated repurposing auranofin in studies, revealing the promising anticancer effects of auranofin in various cancer types [54,56,62,64,[116][117][118][119][120][121] alone or as drug combination [46][47][48]. The only clinical trial using auranofin in GBM tested the combination of nine repurposed drugs including auranofin and temozolomide in the CUSP9v3 Treatment Protocol (NCT02770378) for a limited cohort of 10 patients with recurrent GBM.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with auranofin at 3 µM for 24 h significantly increased ROS levels in the three isogenic cell lines compared to their respective controls (U87MG p < 0.001, U87EGFRwt, p = 0.024, U87EGFRvIII p < 0.001) (Figure 2A). Of note, ROS increase was more pronounced in U87/EGFRvIII compared to U87/EG-FRwt (p = 0.033), as shown in Figure 2A Next, we used N-acetylcysteine (NAC), a conventional ROS scavenger [47,58], to determine whether ROS mediate the cytotoxic effects of auranofin in U87/EGFR isogenic cell lines. NAC treatment at 1 or 2 mM for 72 h did not significantly affect cellular metabolic activity or vitality (Figure S3A).…”
Section: Auranofin Increased Ros Along With Ros-dependent Cytotoxicit...mentioning
confidence: 96%
See 1 more Smart Citation
“…Auranofin is a gold-based compound approved by FDA for rheumatoid arthritis in 1985. Growing evidence has suggested that the drug demonstrates therapeutic effects for infectious diseases ( Capparelli et al, 2017 ; Tunes et al, 2020 ; Wallis et al, 2021 ) as well as for cancers ( Steers et al, 2022 ; Szeliga and Rola, 2022 ). Clinical trials using auranofin for cancer therapy are undergoing (NCT03456700, ovarian cancer; NCT01737502, lung cancers).…”
Section: Discussionmentioning
confidence: 99%